Relative worth of Factors Affecting Acquisition in Libraries of Higher Educational Institutions - Pandiya, Nirnimesh; Sinha, Manoj Kumar (Journal of Information and Knowledge, 2021)
New e-resources are believed to affect preferences of readers and hence acquisition policy of libraries in general and preference for resources in particular need to be tuned accordingly. The paper reports a study undertaken to determine priorities of factors and their components in library acquisition. The literature review has been done by searching in Emerald, Taylor and Francis and Web of Science using PRISMA protocol to understand the past research in this direction. A closedended structured questionnaire designed for the purpose with factors and their components of acquisition, pilot-tested and used for collection of primary data from library professionals of selected institutions of higher education governed and funded by Government of India. The data so collected was analyzed using SPSS 23 to determine and prioritize the factors and their components based on mean scores. The study concluded that policy makers need to focus more on the high ranked factors and their components of acquisition for cost-efficiency, cost-effectiveness and better service to the intended users.